Konstruksi Peran Perempuan dalam Ambivalensi Pemberdayaan Simbolik dan Reproduksi Makna Patriarki: Analisis Wacana Kritis Video Klip Ariana Grande “Positions” - Hakim, Rahman; Sonjaya, Muhamad Risqi Mei (Jurnal Audiens, 2026)
The construction of women in popular media, such as music videos, often reproduces patriarchal values despite being framed within seemingly progressive narratives of empowerment. The positioning media as a space of ideological contestation shaped by power relations. This study examines how the visual text and lyrics of Ariana Grande’s Potitions interact with discursive practices and their socio-cultural context. Unlike previous studies focusing on women as passive objects, this study uncover the paradox of sumbolic empowerment, where women occupy strategic positions in the public sphere yet remain constrained within patriarchal systems. Using a qualitatative approach, the analysis applies Fairclough’s three-dimensional framework of text, discursive practice, combined with a liberal feminist perspective. Analysis was conducted across all scenes, examining camera framing, costume, visual blocking, and lyrical diction. The findings reveal that women’s roles are constructed through a multitasking form of empowerment, with women occupying strategic public positions while remaining embedded within patriarchal oppression. This study reinforces the argument that media is not a neutral space, but an arena of meaning production shaped by power relations and market interest